Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Model PISA Pada Domain Konten Berdasarkan Gaya Belajar - Setiawan, Arie; Kana Hidayati; Yufida Afkarina Nizar Isyam (Jurnal Pendidikan Indonesia, 2024)
Indonesian students' PISA results in the field of mathematics are still relatively low and students are not yet accustomed to questions characterized by real contexts such as PISA questions, so students often make mistakes in solving PISA model questions. This research aims to describe students' mistakes in solving PISA model questions in the content domain. in terms of learning style. This research is an exploratory descriptive research with a quantitative and qualitative approach. The sample in this study was high school students. The sample in this research was determined using techniques stratified proportional random sampling. Data analysis was carried out by calculating the percentage of errors based on student test results, testing differences in the number of students' errors in solving PISA model questions in terms of learning styles using the Anova test. The research results show that overall, the errors of students with a visual learning style are in the medium category while the errors of students with auditory and kinesthetic learning styles are in the high category. However, inferentially, there is no significant difference in the number of student errors in solving PISA model questions between students with visual, auditory and kinesthetic learning styles. Therefore, this study suggests that teachers should provide non-routine questions in learning. This is to reduce errors made by students when solving problems. In other words, giving non-routine questions can improve students' problem solving abilities. The implications of this research are able to identify types of errors based on student learning styles, so that the learning interventions provided can be more targeted and effective.